Pesantren Based Entrepreneurship: Laundry Business and Socio-Economic Impact at Imam Syafi’i Islamic Boarding School Brebes - Anaty (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2025)
This research examines the management practices and socio-economic contributions of the laundry business unit at Pondok Pesantren Imam Syafi’i Brebes, Central Java, Indonesia. Serving as one of the pesantren’s entrepreneurial ventures, the laundry unit not only meets students’ daily needs but also enhances the institution’s financial resilience. Adopting a descriptive qualitative method, data were gathered through in-depth interviews with pesantren leaders, laundry operators, and students, complemented by participant observation and institutional records. The study highlights that the laundry service alleviates students’ domestic responsibilities, enabling them to concentrate on essential activities such as learning and Qur’an memorization. In addition, the unit generates revenue that supports pesantren operations, assists disadvantaged students, and extends services to the local community, thereby fostering stronger socio-economic ties. Guided by Islamic business ethics honesty, trust, and transparency the laundry demonstrates that, despite challenges in facilities and staffing, it holds promise as a pesantren based entrepreneurial model integrating economic empowerment with spiritual and social values.